Assessing the Factors Influencing Service Innovation Capabilities and Performance - Omar, Nor Asiah; Nazri, Muhamad Azrin; Alam, Syed Shah; Ahmad, Azhar (Information Management and Business Review, 2016)
Innovation has been recognized as a central source of business growth and a key determinant of competitive advantage for many organizations. This paper seeks to address two main objectives. The first objective is to examine the direct effect of organizational structure (i.e. centralization and formalization), transformational leadership, organizational learning and customer orientation on innovation capabilities. The second objective is to examine the effect of innovation capability and organizational performance. Findings show that customer orientation, organizational learning, and transformation leadership had significant positive effects on innovation capability. The results further show that innovation capability had a significant impact on organizational performance.